Does Peer Teaching Help Students in Mastering the Present Perfect Tenses? - Safra Apriani Zahraa; Ari Satria; Halim Dwi Putra (STAIN Bengkalis, 2021)
This study focused on the use of peer teaching technique to improve students’ mastery on present perfect tense. The research method used was a Classroom Action Research (CAR). The research data included the results of the pre-test and post-test regarding the present perfect tense. The data collection techniques used were classroom observation, interviews, pre-test, and post-test. The results of this study showed that the average score of students was 31.2 in pretest, increased from 60.7 in Cycle I to 88.3 in Cycle II. It indicated that the use of peer teaching technique could improve students' understanding in mastering the present perfect tense. This technique can be one of the effective ways for lecturers in teaching tenses especially present perfect tense.